No Severe Adverse Effects from Intravitreally Injected Putative Adipose Tissue-Derived Stem Cells - Carsten Faber; Steffen Heegaard; Jens Folke Kiilgaard (Case Reports in Ophthalmological Medicine)
This study reports findings from a 56-year-old patient, who had received bilateral intravitreal injection of putative adipose tissue-derived stem cells at a private clinic in India with the promise of treatment of NAION. During an observation period of 8, respectively, 18 months, the intravitreally injected cells remained silent in the vitreous bodies without either therapeutic effects or complications. The cells cleared with vitrectomy without evidence of integration in the optic nerve or retina. Contrary to recent reports on patients receiving intravitreal injections of similar putative stem cells with the aim of treating AMD, our patient suffered no devastating ocular consequences. Summary. Contrary to recent reports, this case demonstrated no devastating consequences of intravitreal injection of adipose tissue-derived stem cells during an observation period of up to 18 months. After vitrectomy, the cells cleared without evidence of either harm or integration.